(untitled) (Вісник: Міжнародні відносини, 2021)
A thorough study of research papers in Ukrainian, English, German, Spanish, French and other languages on the problems of glocalization is conducted. Based on the abovementioned, 46 interpretations of the term "glocalization" are identified, including 4 own ones. Existing interpretations of glocalization are systematized and classified according to scientific approaches. Prospects for further researches of the world economy and international economic relations on the basis of the results obtained in the article are outlined.